(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This text shares my teaching experience in the Characterization course, offered in the Theater program at the Federal University of Uberlândia (UFU), during the years 2017 and 2018. The writing contextualizes the account, presenting the path I proposed for teaching-learning-creating stage characterization, specifically makeup, in higher education. Furthermore, it highlights the proposed exercises and the artistic-pedagogical tactics developed, connecting knowledge about makeup with different aspects of theatrical staging and pedagogical practices in Theater. To this end, photographic records of the classes and the final projects developed by the students throughout the semesters are used as supporting material.